2008
DOI: 10.2334/josnusd.50.205
|View full text |Cite
|
Sign up to set email alerts
|

Keratocystic odontogenic tumor: a retrospective study of 183 cases

Abstract: Aim: The purpose of this retrospective study was to evaluate the clinicopathological features of 64 patients with keratocystic odontogenic tumor (KCOT). Materials and Methods: The patients ranged in age at the time of diagnosis from 8 to 74 years (mean: 38.20 ± 16.71). Postoperative follow-up period was 3-8 years (mean time 4.76 ± 1.10). This research was carried out on panoramic radiographs and histopathological samples. Data such as gender, age, treatment methods, location of the tumor, presence of impacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
112
6
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(149 citation statements)
references
References 24 publications
17
112
6
10
Order By: Relevance
“…13,[18][19][20] We verified that the mean age of KCOT cases was 35 years, and that the posterior mandible was the most affected site. Data found in our study corroborate the data found in other studies, 13,18 and we found a greater prevalence for the male gender, in agreement with the results reported by Jing et al 19 and González-Alva et al 21 The association of KCOT with NBCCS was seen in 40% of the cases, which is very different from what was reported by González-Alva et al, 21 who only found an association of 6%. The same study reported data on the characteristics of the cases associated with NBCCS, reporting a greater prevalence in female patients (63.6%), which was different from the observations of the present study, wherein we found a higher prevalence in male patients (57% of cases associated with NBCCS).…”
Section: Discussionsupporting
confidence: 38%
“…13,[18][19][20] We verified that the mean age of KCOT cases was 35 years, and that the posterior mandible was the most affected site. Data found in our study corroborate the data found in other studies, 13,18 and we found a greater prevalence for the male gender, in agreement with the results reported by Jing et al 19 and González-Alva et al 21 The association of KCOT with NBCCS was seen in 40% of the cases, which is very different from what was reported by González-Alva et al, 21 who only found an association of 6%. The same study reported data on the characteristics of the cases associated with NBCCS, reporting a greater prevalence in female patients (63.6%), which was different from the observations of the present study, wherein we found a higher prevalence in male patients (57% of cases associated with NBCCS).…”
Section: Discussionsupporting
confidence: 38%
“…Although cases of calcifying epithelial odontogenic tumour were reported in majority of the studies conducted on other populations (Ladeinde et al, 2005;Guerrisi et al, 2007;Gonzalez-Alva et al, 2008;Saghravanian et al, 2010) but not a single case of it was noticed in the mentioned period of our study.…”
Section: 3327 Clinicopathological Evaluation Of Odontogenic Tumours mentioning
confidence: 46%
“…It also showed predominance for males (72.9%) and a marked predilection for posterior mandible (72.9%). These on Japanese population (Gonzalez-Alva et al, 2008). Contrarily a Brazilian study by Avelar et al (2008) stated its prevalence in 3 rd and 4 th decades, dominance for females and involvement for mandibular region mainly.…”
Section: 3327 Clinicopathological Evaluation Of Odontogenic Tumours mentioning
confidence: 99%
“…Les kératokystes présentent un taux de récidives comparable à celui des améloblastomes. Selon certaines études, le taux de récidive peut atteindre 62 % des cas [11]. La récidive des kératokystes serait plus élevée pour la localisation mandibulaire, lorsque le kératokyste est de type parakératosique, que son aspect radiologique est multiloculaire et que l'exérèse a été réalisée en plusieurs fragments [12].…”
Section: Discussionunclassified